The pros and cons of interactive marketing to consumers and the manufacturer. Плюсы и минусы интерaктивного мaркетингa для потребителей и производителей (Journal of Economic Research & Business Administration, 2016)
In the article considered the main pros and cons of interactive marketing to consumers and producers in terms of technical and scientific progression in the spheres of social and economic communication. Many foreign and domestic scientists are considered interactive marketing in isolation, as one of the elements of marketing communication in the organization. However, in modern conditions of development of innovative technologies interactive marketing should not be considered as an element of marketing communications and should be treated as an independent direction in system of marketing communications. In this regard, the consideration of interactive marketing and its advantages and disadvantages with the scientific and theoretical side is of great importance in terms of establishing communications between the producer and the consumer. The importance of interactive marketing for organizations is determined by its advantages and disadvantages. Considering results of research we can say that the main pros of interactive marketing for consumers and producers is this: convenience of buying and selling, activity of consumers in economic processes, minimality of external impact on process of purchase and sale, ease of process of communication and informing, decrease in expenses of the organizations (rent, providing shop, insurance, municipal expenses), drawing up database of accurate consumer needs. Any system or mechanism along with the pros has its cons. The main cons of interactive marketing for consumers and producers the following: risk of loss of electronic information, information overload on the Internet, low level of availability of the Internet, use of personal information on consumers by the organization without their consent, leak of classified information, etc.